OP0140 Circulating Carboxy-Terminal Type X Collagen Fragments (C-Col10), a Measure of Skeletal Hypertrophy, are Elevated in Patients with Osteoarthritis and Ankylosing Spondylitis. (23rd January 2014) - He, Y.; Brandt-Hansen, N.; Wang, J.; Su, D.; Zheng, Q.; Petersen, K.; Simonsen, O.; Schett, G.; Karsdal, M.; Bay-Jensen, A. C.
Abstract : Background: Ankylosing Spondylitis (AS) is a chronic inflammatory disease of the spine and sacroiliac joints, whereas osteoarthritis (OA) is generally considered as a non-inflammatory condition of the synovial joints, predominantly knee and hips. Chondrocyte hypertrophy and cartilage calcification are key pathological events in both joint diseases. Elevated expression of network-forming type X collagen (ColX) is believed to be a specific signal for chondrocyte hypertrophy. Objectives: The objectives of the study were to: i) to develop and validate an ELISA for measurement of serum levels of ColX, and ii) to investigate the levels of ColX in serum of controls, AS and OA patients. Methods: A monoclonal antibody (mAb) was raised against the C-terminus of NC1 domain of ColX. The mAb was characterized by western blot using U2-OS cell as positive control and by immunohistochemistry on human OA knee cartilages sections. A competitive ELISA was developed, C-Col10. The specificity, sensitivity, precision and accuracy were recorded. Serum samples from 342 patients with symptomatic OA (mean KL 2.0[1.9-2.1], 17 AS (mean mSASSS 4.1 [2.8-5.4]) and 8 controls. Mann-Whitney test was used and data is shown as mean [95%>CI]. Results: A strong 32KDa band was identified by western blotting in serum of elderly patients, whereas it was markedly weaker younger controls. This confirmed in lysate of the US-02 cells. The C-Col10 assay was specific for the 6 C-terminal amino acids (LVAPMA) and not for a truncated sequence (SGFLVM), making it a true C-terminal assay. Immuno-staining of OA articular cartilage biopsies, including subchondral bone, showed a clear staining of the deep zone cartilage matrix surrounding the pre-hypertrophic chondrocytes. Marked staining was also observed around the chondrocyte clusters close to the fibrillated surface of the cartilage. The data validate the mAb and support the importance of ColX in OA pathology. The measuring range of the C-Col10 assay was 20-500pg/ml, with intra- and inter-assay CVs of 4.2% and 13%. There was a trend towards increasing ColX level with increasing KL score: KL0 56[27-86]pg/ml, (n=9); KL1 67[57-78]pg/ml, (n=59); KL2 88[75-100]pg/ml, (n=143); KL3 84pg/ml, (n=34), and KL4 91[50-132]pg/ml, (n=21). There was a significant difference between the KL0/1 and KL4 groups (p<0.05). The mean serum Col X level in AS patients was 240[144-334]pg/ml, which was significantly higher than both the OA patients (p<0.01) and the controls (p<0.001). Conclusions: ColX expression represents an essential step in the pathology of joint degenerative diseases. Measurement of ColX may be used as a biomarker of chondrocyte hypertrophy and calcification as well as subchondral remodeling in both OA and AS, may provide essential information on disease progression. Disclosure of Interest: Y. He Employee of: Nordicbioscience, N. Brandt-Hansen Employee of: Nordicbioscience, J. Wang Employee of: Nordicbioscience Beijing, D. Su Employee of: Nordicbioscience Beijing, Q. Zheng Employee of: Nordicbioscience Beijing, K. Petersen: None Declared, O. Simonsen: None Declared, G. Schett: None Declared, M. Karsdal Shareholder of: Nordicbioscience, A. Bay-Jensen Employee of: Nordicbioscience